Blood group discrepancy in mixed-type autoimmune hemolytic anemia in a pediatric patient - Minal Wasnik; Saurabh Lahare; Tushar Jagzape; Ramesh Kumar Chandrakar (Asian Journal of Transfusion Science, 2021)
Autoimmune hemolytic anemia (AIHA) is characterized by the presence of antibodies directed against self-antigens on red blood cells (RBCs) leading to progressive RBC destruction along with reduced red cell survival. Mixed-type AIHA is characterized by the presence of both warm and cold-autoantibodies. These autoantibodies may cause blood-group discrepancy or cross-match incompatibility leading to delay in arranging suitable blood unit for transfusion. The detection of autoantibodies by monospecific-direct antiglobulin test showing positive reaction on immunoglobulin G and C3d and presence of cold-agglutinins leads to the diagnosis. We report a rare case of mixed AIHA in a 15 years female showing severe anemia, blood group discrepancy, and cross-match incompatibility. She received transfusion of least incompatible packed RBCs without any untoward effect.